Investigation of elastomeric materials for bolus using stereolithography printing technology in radiotherapy. (28th May 2020) - Munoz, Luis; Rijken, James; Hunter, Morgan; Nyathi, Thulani
Abstract: Purpose : An investigation was conducted of an elastomeric material, VisiJet M2 (3D systems, USA) for use as 3D bolus within high energy photon beams for radiotherapy. Personalized conformal bolus material on complex structures like the nose can be challenging. This material was evaluated for its clinical feasibility due to its pliability and comfort compared to alternatives. Method : Regular slabs of bolus were created of various thicknesses for dosimetric and non-dosimetric characterization. Verification culminated with the creation of a custom nose bolus for an end to end verification using an anthropomorphic head phantom. In vivo dosimetry using Gafchromic EBT3 (Ashland, USA) film validated delivered doses from a 6 MV conformal field and a pair of 6 MV volumetric modulated arc therapy (VMAT) beams. Results & Conclusion : Non-dosimetric and dosimetric tests were conducted to assess clinical suitability. The bolus was precisely created using stereolithographic (SLA) methods and presented a compliant and uniform water equivalent material with elastic memory. Measurement yielded a physical density of 1.10 g cm −3 and 1.06 relative to water electron density, and the bolus to skin distance was measured to be a maximum of 3 mm. A maximum measured dose difference of <2% was observed for dynamic treatment. Based on the investigation conducted, and the benefits presented for patient comfort while being uniform and water equivalent, and correctly represented within the treatment planning system (TPS), this material has the potential for clinical use for patient specific custom bolus.